Gambaran Kesiapsiagaan Masyarakat dalam Antisipasi Bencana Banjir Di Kecamatan Danau Kerinci Barat Kabupaten Kerinci - Gustini, Sri; Subandi, Andi; Oktarina, Yosi (Jurnal Ilmiah Ners Indonesia, 2021)
Flood disaster is one of the biggest disasters in the world. It is hoped that the readiness and knowledge of the community in dealing with floods is expected to be proactive in being able to take preventive, emergency response and rehabilitation measures in collaboration with the government to maintain the environment that can cause flooding in order to minimize the impact it causes. The magnitude of the potential for flooding in Kerinci prompted the need for community preparedness measures to reduce losses due to these impacts. This study aims to determine the description of community preparedness in anticipation of flood disasters in Danau Kerinci Barat District, Kerinci Regency. This type of research used a quantitative descriptive design. This research was conducted in 5 villages located in the West Lake Kerinci District, namely, the villages of Tanjung Pauh Mudik, Pancuran Tiga, Punai Merindu, Bukit Pulai and Sumur Jauh. The population of all family heads in the 5 villages was 1,580 with a sample size of 110 samples. Technique Sampling used Cluster Random Sampling The results showed the parameters of knowledge are classified as very ready, the parameters for policies and guidelines are not ready, the parameters for the emergency response plan are classified as less ready, the parameters for disaster warning are classified as less ready, and the parameters for resource mobilization are classified as not ready. It can concluded that the description of community preparedness in anticipation of flood disasters in Danau Kerinci Barat District, Kerinci Regency is classified as almost ready.